The Influence of Problem-Based Learning-Flipped Classroom (PBL-FC) on Mathematical Argumentation Skills - Erita, Selvia (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study examines the influence of the Problem-Based Learning-Flipped Classroom (PBL-FC) model combined with learning independence on students' mathematical argumentation skills. Utilizing a quasi-experimental design, the research involved 42 fourth-semester students from IAIN Kerinci, randomly selected from 66 students. The study employed tests and questionnaires to assess the students' argumentation skills and learning independence. Results indicated that the PBL-FC model significantly improved the students' argumentation skills, with an average score of 70.2 compared to 62 in the control group. Statistical tests of the between-subject effect yielded a significance of 0.003 (sig < 0.05), confirming a notable difference in argumentation skills. Furthermore, a significant interaction effect was observed between learning independence and mathematical argumentation skills. Thus, integrating the PBL-FC model with learning independence effectively enhances students' argumentation skills. Future research should investigate applying the PBL-FC model to other subjects to evaluate its effectiveness broadly.